2020
DOI: 10.1107/s2053230x20001168
|View full text |Cite
|
Sign up to set email alerts
|

The thermodynamic profile and molecular interactions of a C(9)-cytisine derivative-binding acetylcholine-binding protein from Aplysia californica

Abstract: Cytisine, a natural product with high affinity for clinically relevant nicotinic acetylcholine receptors (nAChRs), is used as a smoking‐cessation agent. The compound displays an excellent clinical profile and hence there is an interest in derivatives that may be further improved or find use in the treatment of other conditions. Here, the binding of a cytisine derivative modified by the addition of a 3‐(hydroxypropyl) moiety (ligand 4) to Aplysia californica acetylcholine‐binding protein (AcAChBP), a surrogate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…For (À)-hosieine-A the K d values are 0.025 AE 0.005 mM (molar ratio 0.7:1) and 0.040 AE 0.001 mM. These values indicate a much higher affinity for the protein compared with (À)-cytisine, for which ITC-derived K d values of 1.6 mM and 0.60 AE 0.03 mM are reported (Table 4; Rucktooa et al, 2012;Davis et al, 2020). For comparison, varenicline is reported to have a K d of 0.34 mM obtained by ITC (Rucktooa et al, 2012).…”
Section: Binding Studiesmentioning
confidence: 92%
See 1 more Smart Citation
“…For (À)-hosieine-A the K d values are 0.025 AE 0.005 mM (molar ratio 0.7:1) and 0.040 AE 0.001 mM. These values indicate a much higher affinity for the protein compared with (À)-cytisine, for which ITC-derived K d values of 1.6 mM and 0.60 AE 0.03 mM are reported (Table 4; Rucktooa et al, 2012;Davis et al, 2020). For comparison, varenicline is reported to have a K d of 0.34 mM obtained by ITC (Rucktooa et al, 2012).…”
Section: Binding Studiesmentioning
confidence: 92%
“…Structures were solved by molecular replacement using Phaser (McCoy et al, 2007). The initial polypeptide model for the AcAChBP-(+)-anatoxin-a complex structure comprised two pentamers of an AcAChBP structure (PDB entry 2byn; Davis et al, 2020). Once refined, the polypeptide of the complex provided the starting model for the isomorphous AcAChBP-(À)-hosieine-A structure.…”
Section: Structure Determination and Refinementmentioning
confidence: 99%
“…Bispidine-type ligands, in contrast, are readily obtained and more easily derived, without a significant loss of bridged bicyclic 1,3-diamine-based rigidity. (−)-Cytisine 3 , a fusion of bispidine with 2-pyridinone, is well recognized as a nicotinic acetylcholine receptor (nAChR) of the central nervous system and used as a smoking cessation drug . Except for its biological and pharmaceutical uses, O’Brien et al have utilized (−)-cytisine in the semisynthesis of (+)-sparteine surrogate 4 , shown in Figure , which exhibits a similar yield and a similar enantioselectivity in several asymmetric syntheses compared to those of (+)-sparteine.…”
Section: Introductionmentioning
confidence: 99%